Feline Unilateral Hip Dislocation and Contralateral Limb Fractures: : Long-Term Outcomes - Saylak, Nahit; Ersöz Kanay, Berna; Yayla, Sadık; Çatalkaya, Emine; Altan, Semih; Kaya, Ufuk (Acta Scientiae Veterinariae, 2025)
Background: Coxofemoral dislocation accompanied by a contralateral long bone fracture is a rare and challenging orthopedic condition in feline patients. It typically resulted from high-rise syndrome, which involves falling from significant heights, and often required complex surgical and postoperative management. While femoral head and neck excision (FHNE) was a widely accepted salvage procedure for coxofemoral luxation, particularly when primary joint reconstruction was not feasible or economically viable, there had been limited information regarding its long-term functional outcomes in cases involving additional orthopedic trauma. In such multifocal injuries, optimal recovery depended not only on surgical precision but also on postoperative rehabilitation, neuromuscular adaptation, and caregiver compliance. The present study aimed to investigate and compare long-term clinical outcomes of FHNE alone and in combination with simultaneous fracture osteosynthesis in cats, using objective clinical data and subjective owner-reported evaluations. Materials, Methods & Results: This retrospective study reviewed the medical records of 72 cats diagnosed with traumatic unilateral coxofemoral dislocation between 2020 and 2024. Most injuries (82%) were associated with high-rise syndrome. Forty-eight cats (66.6%) that met the inclusion criteria were enrolled. Group I (GI, n = 14) underwent FHNE alone, and Group II (GII, n = 34) received FHNE combined with stabilization of contralateral long bone fractures using intramedullary pins, locking plates, or external fixators. Cats ranged from 1 to 9 years of age and were of both sexes. Follow-up evaluations continued over the long term, including physical examinations, gait observations, and standardized owner interviews. The early complication rate was 42.8% in GI and 17.6% in GII, whereas the total long-term complication rate across both groups was calculated as 25%. Functional outcomes in GII were significantly better during the initial two postoperative weeks (P < 0.05). GI cats displayed prolonged disuse of the operated limb, accompanied by moderate-to-severe muscle atrophy. In contrast, GII cats engaged both hind limbs earlier and showed milder atrophy and faster return to normal locomotion. Clinical evaluations confirmed reduced lameness and improved postural balance in GII. Owner feedback was consistent with these findings, indicating higher satisfaction, earlier weight bearing, and more complete recovery in GII. Discussion: The findings suggest that combining FHNE with concurrent fracture stabilization promotes earlier functional recovery and reduces muscle wasting in cases involving bilateral hindlimb injury. Bilateral limb usage may enhance symmetrical weight distribution, prevent disuse syndrome, and support neuromuscular adaptation during the rehabilitation period. Integrated surgical approaches, especially in polytrauma cases, appear crucial to restoring mobility and quality of life in feline patients. Moreover, strong alignment between clinical assessments and owner perceptions reinforces the value of incorporating subjective quality-of-life indicators in orthopedic outcome evaluations. The study also observed that early postoperative limb use had a positive impact on the overall recovery process. This therapeutic combination may serve as a practical and effective strategy for veterinarians managing multifocal orthopedic injuries in feline trauma patients, particularly those resulting from high-rise syndrome. Keywords: atrophy, cat, coxofemoral luxation, fracture, long-term FHNE results.